Methodology for Creating an Information Tool for Animal Food Facilities. Issue 3 (3rd July 2019) - Evanson, Jessica F.; Alexander, Catherine Y.; Sampedro, Fernando; Boyer, Timothy; Nault, André J; Goldsmith, Timothy J.
Abstract: The U.S. Food Safety Modernization Act, administered by the Food and Drug Administration (FDA), requires animal feed and pet food facilities to conduct a hazard analysis by identifying and evaluating potential hazards in animal food. This paper describes the creation of an information tool designed to help animal food facilities comply with this requirement. A thorough search of the scientific literature and FDA recall data identified the occurrence of hazards in animal food, assessed the severity of the hazards, and provided a scoring system useful for the identification and prioritization of specific animal food-hazard-species combinations.